Teaching and Learning Projects as ’Heterotopias’ - Gosling, David (Critical Studies in Teaching and Learning, 2023)
Using the lens of Foucault’s ideas about heterotopias, this paper discusses the Centres for Excellence in Teaching and Learning (CETLs) which were teaching and learning projects funded between 2005 and 2010 by the Higher Education Funding Council for England (HEFCE). The paper explores the ’location’ of the CETLs in different kinds of real, social and imagined space. This enables an examination of the ways in which CETLs were both ’within’ and ’without’ their institution, both reflecting the institutional culture which created them and yet were also necessarily ’other’. The paper concludes with some speculation on some characteristics of funded teaching and learning projects in general which are illuminated by the issues the CETLs faced about their location, their place, and their identity.